2022
DOI: 10.3390/soilsystems6030057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four-Week Exposure to Salt Treatments on Germination and Growth of Two Amaranthus Species

Abstract: Soil salinity represents one of the most restrictive environmental factors for agriculture worldwide. In the present study, the salt tolerance of two weeds of the genus Amaranthus, A. albus and A. hybridus, the latter cultivated as green vegetable in Africa, were analysed. Both species showed a remarkable salt tolerance phenotype during germination and vegetative growth. To evaluate the percentage and rate of germination, seeds were germinated in Petri dishes in a germination chamber under increasing concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Germination time (MGT) did not vary from the control. Salt and osmotic stress tolerance were reported in other invasive weeds of different genera, such as, Araujia [ 15 ], Amaranhus [ 14 ], Chenopodium [ 69 ], and Cenchrus [ 70 ], which thrive in disturbed habitats (either altered by natural or anthropogenic forces) due to increased plant fitness through functional and adaptive traits [ 71 ]. The stronger effects of NaCl than of PEG can be explained by the ionic toxicity, as salinity has a toxic component in addition to the increased external osmotic potential that reduces water uptake during imbibition also produced by PEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination time (MGT) did not vary from the control. Salt and osmotic stress tolerance were reported in other invasive weeds of different genera, such as, Araujia [ 15 ], Amaranhus [ 14 ], Chenopodium [ 69 ], and Cenchrus [ 70 ], which thrive in disturbed habitats (either altered by natural or anthropogenic forces) due to increased plant fitness through functional and adaptive traits [ 71 ]. The stronger effects of NaCl than of PEG can be explained by the ionic toxicity, as salinity has a toxic component in addition to the increased external osmotic potential that reduces water uptake during imbibition also produced by PEG.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an increasing number of studies are being conducted on responses to drought and salinity not only in model plants, but also in crops and their wild relatives [ 4 , 5 , 6 , 7 , 8 ]. Although unravelling functional responses to environmental factors in invasive plants is gaining interest [ 9 ], analysis of stress tolerance and mechanisms underlying stress responses are scarce in such species [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity induces plant metabolic and molecular changes. A previous study showed that salinity can significantly reduce the rate and final percentages of the germination and emergence of amaranth, resulting in uneven stand establishment and decreased crop yields [33]. A growth reduction was observed in the leaf of amaranth sprouts under saline conditions; such a reduction was associated with a reduction in photosynthetic pigments [34].…”
Section: Cnps Improved Growth Parameters Of Amaranth Sprouts Under Th...mentioning
confidence: 95%
“…Since the source of the problem was in the growing substrate; then, the first suffering organ was the roots, as indicated by smaller root biomass and shorter roots (Liu et al 2021). The uptake of water and nutrients by affected plants becomes restricted and collectively halts the development of aerial organs, including leaf enlargement (Bellache et al 2022).…”
Section: Effects Of Bsf Residue On Red Amaranth Growth and Yieldmentioning
confidence: 99%